Hamstring muscle injury is preceded by a short period of higher running demands in professional football players - Moreno-Perez, V.; Sotos-Martínez, V.; Lopez-Valenciano, A.; Del-Campo, R. L.; Resta, R.; Coso, J. (Biology of Sport, 2024)
The aim of this study was to examine match running patterns before a hamstring muscle injury occurs during a match in male professional football players. A total of 281 male professional football players belonging to 7 teams from LaLiga were prospectively monitored over three seasons. Among these, 36 players suffered a non-contact hamstring muscle injury during an official match. The injuries were recorded by the medical staff, including the minute when the injury occurred. Running distances at different speed thresholds for 5 min and 15 min before the injury were compared to mean values of the previous 5 matches for the same time points. There were a total of 44 non-contact hamstring muscle injuries, which represents a hamstring muscle injury incidence of 3.34 injuries/1000 h of match exposure. The average time loss for these injuries was 33 ± 28 days (range 7 to 117 days). In the 15 min prior to the injury, players ran a similar distance as in control matches (p from 0.22 to 0.08). However, players ran a greater distance in the 5-min period before the injury than in control matches at 21.0-23.9 km/h (p < 0.001) and at = 24 km/h (p < 0.001). The odds ratio for a hamstring muscle injury was 7.147 for those players who ran > 30.0 m at = 21 km/h in a 5-min period (p < 0.001). Hamstring muscle injuries during competition were preceded by 5 min of higher running demands at > 21 km/h, compared with control matches. This suggests that a short period of unusual running increases the risk of hamstring muscle injury in professional football players.